Can Socially Responsible Firms Survive Competition? An Analysis of Corporate Employee Matching Grant Schemes*. (7th June 2017) - Gong, Ning; Grundy, Bruce D
Abstract: Employee matching grant schemes are coordination mechanisms that reduce free-riding by socially conscious employee-donors. Matching schemes coupled with lower take-home pay than offered by non-matching firms will survive capital and labor market competition if employee type is not observable and socially conscious employees are more productive or value working together. Matching can enhance employee welfare and raise more for charity without reducing profits. We document that matching firms have higher labor productivity and are more likely to be ranked as one of the "100 Best" employers. The result is robust to managerial entrenchment concerns and is not confined to the high-tech sector.